Scriptural completion in the Infancy Gospel of James - Bockmuehl, M (Rowman and Littlefield Publishers, 2018)
Every authoritative text—perhaps any significant text—involves its hearers and readers in a process of engagement that invites or even requires the filling of gaps or breaks in what is written.1 In communities committed to canons of Holy Scripture, this engagement may at times appear to outsiders as little more than rationalization—the exposition of a static document in the service of a concern for authorized meaning. Closer observation, however, tends instead to uncover a complex, historically self-renewing process of relating text to intertext; of nuancing the tensions and suspensions of law and poetry and prophecy differentially; of continually rereading multiple senses of the text in light of each other; of the interplay of memory, retrieval, and aggiornamento within an interpreter’s living community of praxis, study, and worship. At the same time, this process sometimes gives rise to a further stage of engagement with authoritative texts, more liminal and yet in other respects more generative than the picture just described. The very genesis of the scriptural texts themselves bears witness to a dynamic process of reception, appreciation, and transmission. In so doing, the sacred page gives rise to new, epiphenomenal text that may either become an integral part of the emerging scriptural voice or alternatively attain an independent authority of its own as a metatext that nevertheless remains associated in some sense with the generative personality of a Moses or an Ezra, a Paul or a John. This process has long been of interest to students of inter-textual and inner-biblical interpretation, of reception history and effective history, in both the Jewish and Christian scriptures.